Sensitivity Analysis of Nanowire FET Biosensor - Yesayan, A.
A nanowire junctionless FET biosensor has been modelled with COMSOL Multiphysics. The high sensitivity of the device in depletion regime was observed. The sensitivity dependence on variations of species concentration in analyte surrounding the nanowire has been studied. It has been demonstrated that the thinner is the nanowire, the higher is the sensitivity and even a single molecule affects the drain current. The model is useful for sensor optimization.
Keywords: Physics